Chemical disinfection of hepatitis A virus on environmental surfaces. - Mbithi, J N (1990)
Hepatitis A virus disinfection was assessed on contaminated stainless-steel disks. Ten microliters of fecally suspended hepatitis A virus was deposited on the center of each disk, dried for 20 min, and then covered with 20 microliters of the test product for 1 min. Of the 20 formulations tested, only 2% glutaraldehyde, a quaternary ammonium formulation containing 23% HCl (toilet bowl cleaner), and sodium hypochlorite (greater than 5,000 ppm [greater than 5,000 micrograms/ml] of free chlorine) reduced the virus titer by greater than 99.9%; phenolics, iodine-based products, alcohols, and solutions of acetic, peracetic, citric, and phosphoric acids were unable to do so.